Kindergarten predictors of third-grade reading and math achievement: The influences of executive function and approaches to learning - Gullo, Dominic F. (American Journal of Education and Learning, 2026)
This study examines how executive function and approaches to learning at kindergarten entry jointly predict longer-term academic outcomes. While each factor has independently been linked to early achievement, less is known about their combined contribution to academic performance by the end of third grade, a critical milestone characterized by increased academic demands and high-stakes testing. Using nationally representative data from the Early Childhood Longitudinal Study–Kindergarten Class of 2010–2011, the study employed hierarchical multiple regression analyses. Executive function skills and approaches to learning were measured at the beginning of kindergarten and reading and mathematics achievement were assessed at the end of third grade. Analyses controlled for socioeconomic status, gender, and age at school entry. Results indicate that both executive function and approaches to learning at kindergarten entry significantly predict third grade reading and mathematics achievement. Models including both predictors demonstrated the greatest explanatory power, revealing that cognitive regulatory skills and learning-related behaviors contribute unique and additive effects to later academic success. Findings underscore the importance of addressing both cognitive self-regulation and learning behaviors in early education. Early screening and intervention efforts that integrate executive function and approaches-to-learning assessments may help identify children at risk for later academic difficulties. Strengthening these competencies in the early years may support more positive and sustained academic trajectories through elementary school.